Evolution of cagA oncogene of Helicobacter pylori through recombination. - Yoshikazu Furuta; Koji Yahara; Masanori Hatakeyama; Ichizo Kobayashi (PLoS ONE, 2011)
Helicobacter pylori is a gastric pathogen that infects half the human population and causes gastritis, ulcers, and cancer. The cagA gene product is a major virulence factor associated with gastric cancer. It is injected into epithelial cells, undergoes phosphorylation by host cell kinases, and perturbs host signaling pathways. CagA is known for its geographical, structural, and functional diversity in the C-terminal half, where an EPIYA host-interacting motif is repeated. The Western version of CagA carries the EPIYA segment types A, B, and C, while the East Asian CagA carries types A, B, and D and shows higher virulence. Many structural variants such as duplications and deletions are reported. In this study, we gained insight into the relationships of CagA variants through various modes of recombination, by analyzing all known cagA variants at the DNA sequence level with the single nucleotide resolution. Processes that occurred were: (i) homologous recombination between DNA sequences for CagA multimerization (CM) sequence; (ii) recombination between DNA sequences for the EPIYA motif; and (iii) recombination between short similar DNA sequences. The left half of the EPIYA-D segment characteristic of East Asian CagA was derived from Western type EPIYA, with Amerind type EPIYA as the intermediate, through rearrangements of specific sequences within the gene. Adaptive amino acid changes were detected in the variable region as well as in the conserved region at sites to which no specific function has yet been assigned. Each showed a unique evolutionary distribution. These results clarify recombination-mediated routes of cagA evolution and provide a solid basis for a deeper understanding of its function in pathogenesis.